Ultrasonic wave generation in two-band organic conductors due to thermoelectric effect - Krstovska, Danica (World Scientific Pub Co Pte Lt, 2017)
A linear thermoelectric generation of a longitudinal ultrasonic wave in organic conductors with two conducting channels, quasi-one dimensional (q1D) and quasi-two dimensional (q2D), is investigated theoretically. The magnetic field and temperature dependences of the amplitude of generated through Nernst effect wave in [Formula: see text]-(BEDT-TTF)2KHg(SCN)4 for two boundary conditions, isothermal and adiabatic are obtained. Findings show a preference of one type of a boundary over another in the wave generation and propagation depending on the magnetic field strength and temperature. At lower temperatures and above B[Formula: see text]=[Formula: see text]4 T, the wave amplitude for adiabatic boundary is smaller compared to the one for isothermal boundary although there is a heat flux through the conductor’s surface in the latter. Both the q1D and q2D charge carriers contribute to the observation of the effect but with different magnitude due to the different drift velocity along the direction of wave propagation.